Summary of the Euratom Collaborative Project FIRST-Nuclides and Conclusions for the Safety Case. (3rd June 2017) - Kienzler, Bernhard; Duro, Lara; Lemmens, Karel; Metz, Volker; De Pablo, Joan; Valls, Alba; Wegen, Detlef H.; Johnson, Lawrence; Spahiu, Kastriot
Abstract: A consortium of 10 partners from seven European countries and the European Commission collaborated in investigating the short-term release of radionuclides from disposed spent nuclear fuel upon canister failure. The Collaborative Project FIRST-Nuclides was implemented in the scope of the 7th Euratom Framework Programme in the period from 2012 to 2014. The objectives and organization of the project are presented, as well as the experiments with highly radioactive materials under investigation. The outcome of the project summarizes the measured instant release fraction (IRF) of safety-relevant isotopes from high burnup spent UO2 nuclear fuels (SNFs). Specifically discussed are the dependencies of the IRF on the sample properties, the gap and grain boundary releases, and the behavior and IRFs of elements such as cesium, iodine, and selenium. The IRFs of nonstandard SNFs were also investigated. The summary is complemented by the presentation of the modeling approaches within the project.